THE INFLUENCE OF PRODUCT PRICE, PRODUCTION VOLUME, AND EXCHANGE RATE TOWARD “NAGAI” EXPORT VOLUME IN PT BINA BUSANA INTERNUSA SEMARANG - Iga H Hardina; Budi Prasetya; Taviyastuti Taviyastuti (Politeknik Negeri Semarang, 2018)
Export volume of spesific product is affected by many factors. Some of them are product price, production volume, and exchange rate. This research aims to find out the influence of product price, production volume, and exchange rate toward export volume of “Nagai” product in PT Bina Busana Internusa Semarang. This research used secondary data in the form of annual and monthly report of sales, production volume, and exchange rate used during transaction for the period of May 2015 – May 2018, so there are 37 samples for this research. Data analysis technique used in this research is multiple linear regression. The result shows that there is a simultaneous effect of product price, production volume, and exchange rate toward export volume of “Nagai”. Partially, product price has negatively effect on “Nagai” export volume. Production volume and exchange rate both give possitive effect on “Nagai” export volume. Production volume is the most influential independent variable compared to product price and exchange rate. Suggestion to increase the export volume of “Nagai” product in short term period is to give an extra attention to production factors and stock opname that will affect directly to production volume.